Medieval Portuguese Royal Chronicles.Topics in a Discourse of Identity and Power - Sousa,Bernardo Vasconcelos e (2007)
It is only in the 15th century that the Portuguese royal chronicles assume their own unequivocal form. The following text analyses them as a discourse of the identity and power of the Crown. Three topics are selected by their importance and salience. These topics are the territory object of observation, the central subject of the narrative and the question of the authors of the historiographical accounts, or rather the position in which the chroniclers place themselves and the perspective they adopt for their description of events.